2017
DOI: 10.1002/wat2.1254
|View full text |Cite
|
Sign up to set email alerts
|

Green infrastructure and its catchment‐scale effects: an emerging science

Abstract: Urbanizing environments alter the hydrological cycle by redirecting stream networks for stormwater and wastewater transmission and increasing impermeable surfaces. These changes thereby accelerate the runoff of water and its constituents following precipitation events, alter evapotranspiration processes, and indirectly modify surface precipitation patterns. Green infrastructure, or low-impact development (LID), can be used as a standalone practice or in concert with gray infrastructure (traditional stormwater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
85
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 131 publications
(87 citation statements)
references
References 82 publications
2
85
0
Order By: Relevance
“…The pollutant removal efficiencies of biofilters at the unit scale are promising, but watershed scale efficacy is less well understood. Watershed-scale implementation of SCMs has been investigated regarding water quantity, but fewer studies have investigated the impacts of watershed-scale installation of SCMs on water quality, 102,103 and only two studies to date have looked at watershed scale effects of biochar-augmented biofilters. 104,105 Studies have generally found that installation of biofilters results in improved water quality at the watershed scale, but these results vary in extent depending on watershed size, climate, impervious area treated, and pollutants of concern.…”
Section: Watershed Scale Implementation Of Biochar-augmented Biofiltersmentioning
confidence: 99%
“…The pollutant removal efficiencies of biofilters at the unit scale are promising, but watershed scale efficacy is less well understood. Watershed-scale implementation of SCMs has been investigated regarding water quantity, but fewer studies have investigated the impacts of watershed-scale installation of SCMs on water quality, 102,103 and only two studies to date have looked at watershed scale effects of biochar-augmented biofilters. 104,105 Studies have generally found that installation of biofilters results in improved water quality at the watershed scale, but these results vary in extent depending on watershed size, climate, impervious area treated, and pollutants of concern.…”
Section: Watershed Scale Implementation Of Biochar-augmented Biofiltersmentioning
confidence: 99%
“…Model selection for assessing the hydrological effects of watershed-scale LID implementation is challenging because it involves trade-offs in achieving the necessary fidelity (i.e., the extent to which the model faithfully represents the modeled system) to hydrological, biological, and biogeochemical processes for prediction accuracy, while minimizing complexity and uncertainty [14]. Careful consideration of these tradeoffs is needed for future work that addresses how LID affects watershed-scale hydrological processes, particularly in mixed land cover systems.…”
Section: Implications For Stormwater Management and Future Researchmentioning
confidence: 99%
“…On the other hand, models that have been explicitly developed to assess the effects of LID practices in mixed land cover watersheds (e.g., VELMA and Regional Hydro-Ecological Simulation System (RHESSys) [66]) may have a strong biogeochemical module (because of their mixed land cover focus) but a more limited hydrological capacity to physically represent LID practices, as compared with a model such as SWMM. Responses to these challenges are evolving by incorporating LID modules within ecohydrological models, such as VELMA, that provide mechanistic representations of LID performance [14] and coupling models to quantify how LID affects the fate and transport of various pollutants, as well as couple SWMM with other watershed models to improve simulations of urban hydrology [67].…”
Section: Implications For Stormwater Management and Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Urbanization replaces natural vegetation cover with impervious surfaces and lawns and alters the natural hydrology of watersheds primarily by reducing infiltration rates and the hydraulic resistance to overland flow and by rapidly discharging surface runoff into rivers and lakes through the storm sewer (Fanelli, Prestegaard, & Palmer, ; Golden & Hoghooghi, ). Generation of more frequent and larger volumes of stormwater runoff, increased streamflow variability, and flashiness as well as decreased watershed lag time are among the most commonly reported hydrological consequences of urbanization (e.g., Booth et al, ; Burges, Wigmosta, & Meena, ; Fanelli et al, ; Loperfido, Noe, Jarnagin, & Hogan, ; Paul & Meyer, ; Yao, Chen, & Wei, ).…”
Section: Introductionmentioning
confidence: 99%